Cost-Effectiveness of Solitaire Stent Retriever Thrombectomy for Acute Ischemic Stroke: Results From the SWIFT-PRIME Trial (Solitaire With the Intention for Thrombectomy as Primary Endovascular Treatment for Acute Ischemic Stroke). Issue 2 (February 2017) - Shireman, Theresa I.; Wang, Kaijun; Saver, Jeffrey L.; Goyal, Mayank; Bonafé, Alain; Diener, Hans-Christoph; Levy, Elad I.; Pereira, Vitor M.; Albers, Gregory W.; Cognard, Christophe; Hacke, Werner; Jansen, Olav; et al.
Abstract : Background and Purpose—: Clinical trials have demonstrated improved 90-day outcomes for patients with acute ischemic stroke treated with stent retriever thrombectomy plus tissue-type plasminogen activator (SST+tPA) compared with tPA. Previous studies suggested that this strategy may be cost-effective, but models were derived from pooled data and older assumptions. Methods—: In this prospective economic substudy conducted alongside the SWIFT-PRIME trial (Solitaire With the Intention for Thrombectomy as Primary Endovascular Treatment for Acute Ischemic Stroke), in-trial costs were measured for patients using detailed medical resource utilization and hospital billing data. Utility weights were assessed at 30 and 90 days using the EuroQol-5 dimension questionnaire. Post-trial costs and life-expectancy were estimated for each surviving patient using a model based on trial data and inputs derived from a contemporary cohort of ischemic stroke survivors. Results—: Index hospitalization costs were $17 183 per patient higher for SST+tPA than for tPA ($45 761 versus $28 578; P <0.001), driven by initial procedure costs. Between discharge and 90 days, costs were $4904 per patient lower for SST+tPA than for tPA ($11 270 versus $16 174; P =0.014); total 90-day costs remained higher with SST+tPA ($57 031 versus $44 752; P <0.001). Higher utility values for SST+tPA led to higher in-trial quality-adjusted life years (0.131 versus 0.105; P =0.005). In lifetime projections, SST+tPA was associated with substantial gains in quality-adjusted life years (6.79 versus 5.05), cost savings of $23 203 per patient and was economically dominant when compared with tPA in 90% of bootstrap replicates. Conclusions—: Among patients with acute ischemic stroke enrolled in the SWIFT-PRIME trial, SST increased initial treatment costs, but was projected to improve quality-adjusted life-expectancy and reduce healthcare costs over a lifetime horizon compared with tPA. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT01657461. Abstract : Supplemental Digital Content is available in the text.